(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The unique feature of the state of Johor that distinguishes it from other states in Malaysia is the existence of its own royal security force known as the Johor Military Force (JMF) or ‘Askar Timbalan Setia Negeri Johor’ (ATSN). The JMF was established in 1886 by the late Maharaja Abu Bakar as contained in the Loyalty Agreement signed by the Johor state government with the British government at the Colonial Office, London. The JMF once served as a state defense fortress besides assisting the police in ensuring security in the state of Johor. With the inclusion of Johor into the Federation of Malaya, JMF has remained until now but its role has shifted to the security of the family of Sultan of Johor and its assets only. Now, after a century, today’s generation is less knowledgeable about the role and historical value that exists with this JMF team that needs to be known and preserved. This article aims to provide an explanation on the existence of the JMF team in more depth to the current and future generations. Library research was used with reference to the printed documents housed in the National Archives of Johor Branch and the Johor Royal Museum in addition to the research on digital media through the ‘History Channel’ documentary. The results of the study show that the existence of this team needs to be fully preserved and further research needs to be done thoroughly to ensure that its historical value continues to be preserved from time to time.